Applied welfare economics cost-benefit analysis of projects and policies - Florio, Massimo 1953- (Routledge, 2023)
"Applied Welfare Economics: Cost-Benefit Analysis for Project and Policy Evaluation presents a consistent framework for applied welfare economics and is grounded in a comprehensive theory of cost-benefit analysis, specifically focused on offering a practical approach to policy and project evaluation. After opening with a theoretical discussion of the concept of social welfare, a critical analysis of the traditional doctrine of welfare economics embodied in the Two Fundamental Theorems, and a presentation of social cost-benefit analysis, the book introduces readers to an applied framework. This includes the empirical estimation of shadow prices of goods, of the social cost of labour and capital, the assessment of risk. This book also discusses the state of the art of international experience with CBA, including ex-post evaluation of major projects, and the use of cost-benefit analysis in regulatory policy. The empirical chapters draw from first-hand research, gained by the authors and his collaborators over many years of advisory work for the European Commission and other international and national institutions. This second edition presents updated data, more international examples, and more coverage of topics such as very long run discounting effects. It also includes end-of-chapter questions to aid student's learning. Applied Welfare Economics is a valuable textbook for upper-level courses on welfare economics, cost-benefit analysis, public policy analysis and related areas"--
First edition published by Routledge 2014
Keywords: Wohlfahrtstheorie; Kosten-Nutzen-Analyse; Welfare economics; Cost effectiveness; Cost-Benefit Analysis; Économie du bien-être; Coût-efficacité; cost benefit analysis